1998
DOI: 10.1080/00380768.1998.10414485
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of protons and solution calcium concentration in phosphate rock dissolution by organic acids

Abstract: A series of experiments was conducted to quantify the relative contribution of protons and other mechanisms to the dissolution of phosphate rocks (PRs) from six countries in solutions of low-molecular-weight-aliphatic organic acids. The amounts of P and Ca released after 3 d of incubation at 28"C were determined in all the experiments. In the first experiment the solubility of the PRs « 500 .urn particle size) in 100 M (25 mL g-l PR) oxalic, tartaric, and citric acids was compared with that in three mineral ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…The amount of P solubilized by P. Fuscum was found to be directly related to pH, while P. Bilaii solubilized more PR than could be accounted for by the pH change, indicating that another mechanism, in addition to H + production, was contributing to PR solubilization. Other authors have found no correlation between the amount of PR solubilized and the pH, supporting the fact that an alternative mechanism of solubilization exists (Cerezine et al 1988, Sperber 1958a, Whitelaw et al 1999, Sagoe et al 1998b). …”
Section: Tionmentioning
confidence: 83%
See 2 more Smart Citations
“…The amount of P solubilized by P. Fuscum was found to be directly related to pH, while P. Bilaii solubilized more PR than could be accounted for by the pH change, indicating that another mechanism, in addition to H + production, was contributing to PR solubilization. Other authors have found no correlation between the amount of PR solubilized and the pH, supporting the fact that an alternative mechanism of solubilization exists (Cerezine et al 1988, Sperber 1958a, Whitelaw et al 1999, Sagoe et al 1998b). …”
Section: Tionmentioning
confidence: 83%
“…Tricarboxylic acids are not always superior to dicarboxylic acids in PR solubilizing ability; Sagoe et al (1998b) found oxalic and tartaric acids, which are dicarboxylic acids, release more P into solution than citric acid. This exception was attributed to the fact that oxalic and tartaric acids form poorly soluble precipitates with Ca 2+ , effectively lowering the solution saturation point (Sagoe et al 1998b). …”
Section: Chelationmentioning
confidence: 99%
See 1 more Smart Citation
“…P-solubilizing activity is related to the microbial production of organic acids, which chelate the cation bound to phosphate, thereby converting it to a soluble form (Sagoe et al, 1998;Rashid et al, 2004;Lugtenberg & Kamilova, 2009). In the present study, a significant negative relationship was observed between the amount of soluble P and pH in the culture medium (R 2 =0.953).…”
Section: Discussionmentioning
confidence: 99%
“…Acidification of the surroundings of microbial cell releases proton through the production of organic acids (Villegas and Fortin, 2002). These metabolite organic acids as a result of anion exchange of P by an acid anion can either directly dissolve the mineral P or can chelate Al 3+, Fe 3+ , Ca 2+ ions associated with inorganic P. The carboxyl and hydroxyl groups chelate the cation bound to inorganic P and convert it into soluble forms (Sagoe, 1998;Seema et al, 2013) with the net result of an enhanced availability of it to the plant. As the soil pH increases the divalent and trivalent forms of inorganic P, HPO 4 -2 and HPO 4 -3 occur in the soil.…”
Section: Phosphate Solubilization and Mineralization By Phosphate Solmentioning
confidence: 99%